Fabrication of a mixed matrix membrane with in situ synthesized quaternized polyethylenimine nanoparticles for dye purification and reuse - Zhu, J.; Zhang, Y.; Tian, M.; Liu, Jian (American Chemical Society, 2015)
© 2015 American Chemical Society. A facile and novel method for the fabrication of mixed matrix membranes (MMMs) has been developed, i.e., in situ synthesis of quaternized polyethylenimine (QPEI) soft nanoparticles (SNPs) followed by quaternization with bromoethane in poly(ether sulfone) (PES) casting solution. The resulting composite membranes were constructed via phase inversion method. The influences of SNPs on the morphology and performance of the hybrid membranes were systematically investigated by scanning electron microscopy, dynamic water contact angle, antifouling measurement, etc. The composite membranes exhibited a thin top layer and porous finger-like structure, which were greatly affected by in situ synthesized SNPs. Contact angle and water uptake measurements indicated that the hydrophilicity of hybrid membranes markedly improved in contrast with that of unfilled membrane. Meanwhile, the water flux of the membranes significantly enhanced due to the incorporation of SNPs. The ion-exchange capacity (IEC) value could achieve as high as 0.72 mmol g-1with an initial PEI content of 1.5 wt %. The salts rejection of MMMs followed the order: MgCl2> MgSO4> Na2SO4> NaCl, confirming that the hybrid membranes were positively charged. Meanwhile, the fouling parameters demonstrated that the composite membranes exhibited a preferable antifouling property. The newly developed membranes demonstrated an impressive prospect for the dye purification due to the high rejection of reactive dyes with a high permeation flux, as well as low multivalent ions retention. The possible separation mechanism of dyes and salts for composite membranes influenced by synthesized SNPs was also proposed in this study.